Chikungunya in the region of the Americas. A challenge for rheumatologists and health care systems. Issue 10 (October 2016) - Pineda, Carlos; Muñoz-Louis, Roberto; Caballero-Uribe, Carlo; Viasus, Diego
Abstract At the end of 2013, the Pan American Health Organization issued an epidemiological alert due to the detection of the first local cases of Chikungunya in the Americas. By August 2015, autochthonous transmissions were detected in 33 countries and territories of the Americas. Latin America has reported nearly one million cases; only Colombia has issued a report of >200, 000 cases during the first 4 months of 2015. In some Latin American and Caribbean countries, Chikungunya becomes a major public health problem. The disease commonly exhibits a self-limited course of arthritis, usually lasting for a few days or that may be prolonged to weeks; however, in 10–60 % of cases, joint pain may become chronic and persist for up to 3–5 years. Human-caused environmental changes, such as climate change, the globalization of international exchange, and disordered urban growth, are some factors that aid in its emergence and dissemination. Outbreaks of Chikungunya comprise a challenge for health care systems and rheumatologists because of the high attack rate on the population and the anticipated development of post-Chikungunya chronic rheumatism. This review emphasizes the rheumatologic clinical manifestations reported in the American continent and highlights the challenges that health care systems face in the absence of an effective vaccine and specific treatment to fight Chikungunya.